CHALLENGES, OPPORTUNITIES AND PROSPECTS OF UNIVERSITY LIBRARIES IN THE GLOBAL SCENARIO OF UNCERTAINTY: UNILIBNSD EDITOR'S VIEW - KOLESNYKOVA, Tetiana O. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2021)
The global scenario of uncertainty caused by the COVID-19 pandemic demonstrated how quickly university libraries can respond to changes in the educational and research ecosystems of their institutions. The new (6th) issue of the journal “University Library at a New Stage of Social Communications Development. Conference Proceedings” is exactly about this. The papers discuss new behaviours / work of library staff based on digital communication technologies, our projects, our goals, our hopes, as well as our doubts and concerns for the maximum contribution of libraries to the development of university communities in a constantly changing world. Full-length articles about the most interesting world library and information practices and ideas were selected, reviewed and recommended by members of the international editorial board of the similarly-named conference (UniLibNSD-2021), which was held in a hybrid format on October 7-8, 2021 in Dnipro, Ukraine. The title “University Library at a New Stage of Social Communications Development. Conference Proceedings” has been accepted in Scopus (2021).